The Palgrave Handbook on Rethinking Colonial Commemorations
XLII, 609 p. 38 illus.
Keywords: The Palgrave Handbook on Rethinking Colonial Commemorations explores global efforts, particularly from Indigenous and Bla(c)k communities, to dismantle colonial commemorations, monuments, and memorials. Across the world, many Indigenous and Bla(c)k communities have taken action to remove, rectify and/or re-imagine colonial commemorations. These efforts have had the support of some non-Indigenous and white community members, but very often they have faced fierce opposition. In spite of this, many have succeeded, and this work aims to acknowledge and honour these efforts. As a current and much-debated issue, this book will present fresh findings and analyses of recent and historical events, including #RhodesMustFall, Anzac Day protests, and the transferral of confederate monuments to museums. Comprising of chapters written by Indigenous, Bla(c)k and non-Indigenous authors, from a wide variety of locations, backgrounds and purposes, this topical volume is a timely andimportant contribution to the fields of memory studies, Indigenous Studies, and cultural heritage. Professor Bronwyn Carlson is an award-winning Aboriginal author, researcher and academic who lives on Dharawal Country in New South Wales. Bronwyn is the author of The politics of identity: who counts as Aboriginal today? (2016) and a well-known commentator on the place of colonial monuments. She is a co-author of Monumental Disruptions: Aboriginal People and Colonial Commemorations in So-Called Australia (2023). She is the founder and editor of The Journal of Global Indigeneity and the Director of the Centre for Global Indigenous Futures, Head of the Department of Indigenous Studies at Macquarie University and a Fellow of the Australian Academy of the Humanities. Dr Terri Farrelly is an Adjunct Fellow and Postdoctoral Research Associate with the Department of Indigenous Studies at Macquarie University. She is a settler researcher and author whose work has been dedicated to Aboriginal suicidologies and addressing racism and discrimination through truth-telling. She is a co-author of Monumental Disruptions: Aboriginal People and Colonial Commemorations in So-Called Australia (2023).